The Cry of the Onlies - Klass, Judy (London Titan Books Ltd, 1989)
Captain Kirk must confront the ghosts of his past to prevent a catastrophic war in this Star Trek adventure.
Keywords: Spock, Mr. (Fictitious character) -- McCoy, Leonard (Fictitious character) -- Kirk, James T. (Fictitious character)